DNA barcoding and phylogenetic analysis of leafhoppers associated with Aster Yellow disease on China aster, Marigold and Chrysanthemum. (17th February 2020) - Hanchipura Mallesh, Mahadeva Swamy; Asokan, Ramasamy; Gadad, Hanamant; Duleep Kumar, Samuel; Kumar, Rajiv; Prakash, Tejaswini
Abstract: The Cicadellidae (Auchenorrhyncha: Hemiptera) are important agricultural, horticultural and ornamental pests. But it is very difficult to define nymphs and female adults using morphological characteristics. This research was aimed at understanding the variety of leafhoppers species and defining the prospective cause of the aster-yellow disease in China Aster, Marigold and Chrysanthemum. Two surveys were conducted in and around Pune, Maharashtra and Bengaluru, Karnataka between November 2016 and February 2017. The mitochondrial cytochrome oxidase subunit I (mtCOI) region marker was used in the species diagnosis and genetic diversity research. Through the use of mtCOI molecular marker eight different leafhoppers species were identified as Sogatella furcifera, Homalodisca insolita, Amrasca biguttula, Balclutha incise and Balclutha abdominalis and Japanagallia trifurcate . Whereas at genus level identified as Toya, Empoasca, Perkinsiella, Hishimonus, Tambocerus, Phaconeura, Curena, Psammotettix and Graphocophala species. These results are strongly corroborated with morphological identification. On the basis of multiple sequence alignment of the mtCOI gene, a species phylogenetic tree with the highest likelihood was drawn. All the leafhopper species clustered together in accordance with the species data collected from the database of the different geographic regions from the NCBI GenBank and Barcode of Life (BOLD). Such results suggest that it is important to use both molecular and morphological methods to ensure accurate identification of organisms. To conclude, this research contributes valuable knowledge to molecular biology and recognizes leafhopper species that serve as major phytoplasma vectors.